2020
DOI: 10.1038/s41420-020-0281-4
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical activity of RAGs is impeded by Dolutegravir, an HIV integrase inhibitor

Abstract: HIV is a retrovirus that infects CD4 + T lymphocytes in human beings and causes immunodeficiency. In the recent years, various therapies have been developed against HIV, including targeting the HIV specific protein, integrase, responsible for integration of HIV cDNA into host DNA. Although, integrase is specific to HIV, it has functional and structural similarity with RAG1, one of the partner proteins associated with V(D)J recombination, a process by which immune diversity is generated in humans. Currently, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…10 In vitro, the impact of dolutegravir on RAG is less than that of elvitegravir but more marked than that of raltegravir. 11 In juvenile rats, postnatal exposure to dolutegravir does not induce any immunological alterations. 12 However, the development of the T and B lymphocyte repertoire begins very early during the fetal period.…”
Section: Discussionmentioning
confidence: 96%
“…10 In vitro, the impact of dolutegravir on RAG is less than that of elvitegravir but more marked than that of raltegravir. 11 In juvenile rats, postnatal exposure to dolutegravir does not induce any immunological alterations. 12 However, the development of the T and B lymphocyte repertoire begins very early during the fetal period.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, it is reasonable to assume that raltegravir might be an inhibitor of RAG1 and RAG2, which play essential roles in V(D)J recombination, oncogenic immunoglobulin gene translocations, and so excessive and abnormal production of monoclonal antibodies in myeloma cells. However, elvitegravir and dolutegravir, two other FDA‐approved retroviral integrases, have recently been demonstrated to inhibit V(D)J recombination and significantly reduce mature B lymphocytes in vivo, unlike raltegravir (Nilavar et al, 2020). Computational docking simulations predicted the highest frequency of interaction between RAG1 recombinase and raltegravir among the other integrase inhibitors (Musat et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, elvitegravir and dolutegravir are other current FDA‐approved integrase inhibitors for HIV‐1 therapy. Recent studies have shown that elvitegravir and dolutegravir could affect the physiological activities of RAG1 by inhibiting both binding and cleavage of RAG1 to RSS in vitro, unlike raltegravir (Nilavar et al, 2020; Nishana et al, 2017). In addition to raltegravir's potential RAG1 and RAG2 inhibitory effect, Metnase fusion protein consisting of the DNA repair component SET histone methylase domain and the transposase nuclease domain derived from the Mariner transposase has been shown to be a target of raltegravir (Williamson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…EMSA was carried out as described previously [ 38 , 83 ]. In brief, radiolabeled DNA substrates were incubated with appropriate proteins in a buffer (1X) containing 22.5 mM MOPS-KOH (pH 7.0), 20% DMSO, 2.2 mM DTT, 50 mM potassium glutamate, 2% (v/v) glycerol and BSA (100 ng/ml) for 2 h at 25°C.…”
Section: Methodsmentioning
confidence: 99%